Cultural significance of wild edible mushrooms in four municipalities of Boyacá (Colombia): Use of edible mushrooms in Boyacá (2023)
The cultural significance of an organism is determined by its value to a group of individuals. In the case of fungi, it has been evaluated using precise indicators that allow comparing ethnomycological knowledge between communities. In Colombia, ethnomycological knowledge is sheltered by peasant and indigenous communities and it is estimated that 70 species are consumed. In this work, the cultural importance of wild edible mushrooms (EMCSI) in four municipalities of Boyacá (San Mateo, Miraflores, Togüí and Pauna) was estimated. Mushrooms are used for food and rarely for medicine; of a total of 20 reported species, the local use of 12 species is evidenced. The fungi with the highest EMCSI were Crepidotus palmarum, Auricularia fuscosuccinea, Ramaria spp., Agaricus aff. trinitatensis and Pleurotus sp.1. The cultural variables that describe traditional knowledge include eight of those considered in the EMCSI, except for the economic index. This work builds a relationship of knowledge in a dynamic way; Community participation involves an exchange of knowledge that should be reflected in the conservation of forests, the appropriation of this provisioning ecosystem service, and the strengthening of interest in traditional knowledge among young people and children.